The behaviour of mosquitoes in relation to humans under holed bednets: the evidence from experimental huts - Seth R Irish (Memorias do Instituto Oswaldo Cruz, 2014)
The physical integrity of bednets is a concern of national malaria control programs, as it is a key factor in determining the rate of replacement of bednets. It is largely assumed that increased numbers of holes will result in a loss of protection of sleepers from potentially infective bites. Experimental hut studies are valuable in understanding mosquito behaviour indoors, particularly as it relates to blood feeding and mortality. This review summarises findings from experimental hut studies, focusing on two issues: (i) the effect of different numbers or sizes of holes in bednets and (ii) feeding behaviour and mortality with holed nets as compared with unholed nets. As might be expected, increasing numbers and area of holes resulted in increased blood feeding by mosquitoes on sleepers. However, the presence of holes did not generally have a large effect on the mortality of mosquitoes. Successfully entering a holed mosquito net does not necessarily mean that mosquitoes spend less time in contact with the net, which could explain the lack in differences in mortality. Further behavioural studies are necessary to understand mosquito behaviour around nets and the importance of holed nets on malaria transmission.